Musculoskeletal Sarcoma: Update on Imaging of the Post-treatment Patient. Issue 1 (February 2016) - Garner, Hillary W.; Kransdorf, Mark J.
Post-treatment imaging of musculoskeletal sarcoma remains challenging, but newer imaging techniques are improving our ability to recognize both local and distant recurrence and accurately distinguish local recurrence from post-treatment change. We review recent advances in dynamic contrast-enhanced magnetic resonance imaging, diffusion-weighted magnetic resonance imaging with apparent diffusion coefficient mapping and positron emission tomography/computed tomography in the post-treatment follow-up of musculoskeletal sarcoma. We also describe our multidisciplinary sarcoma team approach to patient care and the essential role of the radiologist in the clinical follow-up scheme.